From noise to synthetic nucleoli: can synthetic biology achieve new insights?. Issue 4 (11th January 2016) - Ciechonska, Marta; Grob, Alice; Isalan, Mark
Abstract : Synthetic biology builds new systems not only for applications but also to understand biology, achieving fundamental insights in the process. Abstract : Synthetic biology aims to re-organise and control biological components to make functional devices. Along the way, the iterative process of designing and testing gene circuits has the potential to yield many insights into the functioning of the underlying chassis of cells. Thus, synthetic biology is converging with disciplines such as systems biology and even classical cell biology, to give a new level of predictability to gene expression, cell metabolism and cellular signalling networks. This review gives an overview of the contributions that synthetic biology has made in understanding gene expression, in terms of cell heterogeneity (noise), the coupling of growth and energy usage to expression, and spatiotemporal considerations. We mainly compare progress in bacterial and mammalian systems, which have some of the most-developed engineering frameworks. Overall, one view of synthetic biology can be neatly summarised as "creating in order to understand."